No significant links between somatognosia, stereognosia, and hypermobility: sensory processing unlikely to drive common complaints in hypermobile population - Hanzlíková, Ivana; Ruská, Aneta; Jančíková, Kristýna; Hébert-Losier, Kim (BMC musculoskeletal disorders, 2025)
BACKGROUND: Previous research has demonstrated impaired proprioception and poorer responses to tactile deep pressure, visual-tactile integration, and vestibular stimuli in individuals with generalized hypermobility, potentially leading to sensory processing issues. Therefore, we aimed to explore the influence of hypermobility on somatognosia and stereognosia. METHODS: Forty-six participants were assessed using the Beighton score and categorized into three groups: non-hypermobile (n = 20), symptomatic hypermobile (n = 13), and asymptomatic hypermobile (n = 13). Somatognosia was evaluated using the shoulder width test in the vertical plane and pelvic width test in the vertical and horizontal planes. Stereognosia was assessed with Petrie's test. Spearman's rank correlation coefficient was examined the relationship between the Beighton score and measures of somatognosia and stereognosia. An unpaired t-test was used to compare variables between hypermobile (both symptomatic and asymptomatic) and non-hypermobile individuals, while a one-way ANOVA was used to compare data between the three groups. RESULTS: No significant relationship was observed between Beighton scores and measures of somatognosia and stereognosia. The t-test revealed no statistically significant differences between hypermobile and non-hypermobile groups in the shoulder width, two pelvic widths, and Petrie's tests (all p ≥ 0.105). Similarly, one-way ANOVA showed no statistically significant differences between the three groups across these tests (all p ≥ 0.177). CONCLUSIONS: The results indicate that somatognosia and stereognosia are not significantly related to the Beighton score and do not significantly differ between the groups studied. These sensory processing functions are unlikely to contribute to the common complaints reported by hypermobile individuals. CLINICAL TRIAL NUMBER: Not applicable.
Keywords: Young Adult; Asymptomatic hypermobility; agnozie; nestabilita kloubu; Symptomatic hypermobility; Male; Sensory processing; Stereognosis; stereognózie; mladý dospělý; Beighton score; Adult; dospělí; mužské pohlaví; Petrie test; Joint Instability; lidé; ženské pohlaví; Humans; Proprioception; Agnosia; propriocepce; Female; lidé středního věku; Middle Aged